2020
DOI: 10.1111/tri.13753
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐derived cell‐free DNA as a biomarker for rejection after kidney transplantation: a systematic review and meta‐analysis

Abstract: Summary A systematic review and meta‐analysis were performed to investigate the value of donor‐derived cell‐free DNA (dd‐cfDNA) as a noninvasive biomarker in diagnosing kidney allograft rejection. We searched PubMed, Web of Science and the Cochrane Library for original research papers published between January 1994 and May 2020 on dd‐cfDNA fractions in blood of kidney allograft recipients. A single‐group meta‐analysis was performed by computing pooled estimates for dd‐cfDNA fractions using the weighted median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…[ 14 ], among 79 patients with lower grade TCMR/borderline lesion, only 42 patients had elevated dd‐cfDNA (>0.5%), and these patients showed adverse graft function, more frequent de novo DSA formation and future/persistent rejection. In contrast, in a recent meta‐analysis of four studies evaluating dd‐cfDNA in relation to TCMR (35 samples), dd‐cfDNA levels were not elevated [ 17 ]. The elevated fraction of dd‐cfDNA in the single patient with BKVAN may be in line with an earlier report of 10 patients with BK viremia, where dd‐cfDNA levels correlated tightly with viral load and biopsy‐diagnosed BKVAN [ 29 ].…”
Section: Discussionmentioning
confidence: 95%
“…[ 14 ], among 79 patients with lower grade TCMR/borderline lesion, only 42 patients had elevated dd‐cfDNA (>0.5%), and these patients showed adverse graft function, more frequent de novo DSA formation and future/persistent rejection. In contrast, in a recent meta‐analysis of four studies evaluating dd‐cfDNA in relation to TCMR (35 samples), dd‐cfDNA levels were not elevated [ 17 ]. The elevated fraction of dd‐cfDNA in the single patient with BKVAN may be in line with an earlier report of 10 patients with BK viremia, where dd‐cfDNA levels correlated tightly with viral load and biopsy‐diagnosed BKVAN [ 29 ].…”
Section: Discussionmentioning
confidence: 95%
“…With respect to ACR, dd-cfDNA levels were lower in T cell-mediated rejection (TCMR) Banff 1A with median values of 0.2% in the DART study, with similar values demonstrated in another study [ 8 , 10 ]. This finding has been further validated in two meta-analyses showing that dd-cfDNA could not distinguish milder forms of TCMR from no rejection [ 11 , 12 ]. Although utilizing alternate assays of dd-cfDNA may enhance detection of TCMR [ 13 ], it may still lack optimal sensitivity in detecting all cases of TCMR.…”
Section: Current Data and Utility Of Dd-cfdna In Kidney Transplantationmentioning
confidence: 80%
“…However, like in any assay, lowering the cutoff would not only increase sensitivity, but also would lead to an increase in false positive results which may prompt unnecessary anti‐rejection treatment. Similarly, a higher cutoff for the diagnosis of rejection, as suggested by some studies that showed higher median value (2.50%) of dd‐cfDNA fraction in patients with ABMR, would lead to an increase in false negative results 9 . More recently, the combination of the quantity of dd‐cfDNA threshold and the dd‐cfDNA fraction threshold has been suggested to improve sensitivity in the detection of active rejection in renal allograft patients 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a higher cutoff for the diagnosis of rejection, as suggested by some studies that showed higher median value (2.50%) of dd-cfDNA fraction in patients with ABMR, would lead to an increase in false negative results. 9 More recently, the combination of the quantity of dd-cfDNA threshold and the dd-cfDNA fraction threshold has been suggested to improve sensitivity in the detection of active rejection in renal allograft patients. 10 Our analysis is limited by the overall small number of surveillance biopsies performed and the significant number of unacceptable dd-cfDNA samples excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%